Tiger Escape - Naidu, M. Kamal (International Journal of Bio-resource and Stress Management, 2010)
The article presents an incidence of tiger escape in Hyderabad Zoo of Andhra Pradesh state in India as experienced by the author. The story narrates how it was difficult and a risky operation to capture the escaped tiger alive without a ‘tranquillizer gun’ in those days (1977). The story tells how with the wise leadership of the author a team of dedicated people was successful in capturing the escaped tiger alive without any loss of human life. The whole operation required highly coordinated team effort along with trust in knowledge of animal behavior, daring staff, and above all, strict discipline in carrying out the whole operation. The experience provides a unique example of method and approach of wildlife conservation and management.